Evaluasi Website BBMKG Wilayah III Menggunakan User Experience Questionnaire (UEQ) - Juniastra, Made Gde; Artha, I Gede Mony; Gunawan, I Made Agus Oka; Indrawan, Gede (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2025)
The website of the Center for Meteorology, Climatology, and Geophysics (BBMKG) Region III serves as a tool for BBMKG Region III to fulfill its duty of providing meteorology, climatology, air quality, and geophysics information to the public. Continuous website evaluation needs to be carried out to improve website quality to provide optimal service to the community. One of the user experience evaluation method that can be used is the User Experience Questionnaire (UEQ), utilizing a quantitative survey approach in data collection. In this study, 25 respondents from various departments within BBMKG Region III participated. Benchmark results showed that five evaluation scales are in the good category namely Efficiency with a score of 1.55, Perspicuity with 1.83, Dependability with 1.49, Stimulation with 1.36, and Novelty with 1.35. Only one scale, Attractiveness, is in above average category with a score of 1.53. To increase the Attractiveness scale value, the author suggests refreshing the design/appearance of the website, one of which might be by using a web system development framework such as Laravel. It is hoped that by using this framework, the website's appearance will be more dynamic and attractive, and it will also be easier to update the design in the future. Based on the research results, none of the scales reached the excellent category, indicating that improvements in all aspects are necessary to achieve an excellent level.